THE EFFECT OF WORK DISCIPLINE, COMPETENCE, AND EMPLOYEE EMPOWERMENT ON EMPLOYEE PERFORMANCE AT THE DIRECTORATE OF GOODS TRAFFIC, BATAM ENTREPRISE AGENCY (BP BATAM) - Ulfah, Nurul; Sabri, Sabri; Mulyadi, Mulyadi (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of work discipline, Competence, and employee empowerment on employee performance at the Directorate of Goods Traffic of the Batam Business Agency (BP). The study used a descriptive, quantitative approach with a census method, given the relatively small population of 35 employees; thus, the entire population served as respondents. Data were collected through the distribution of questionnaires that had been tested for validity and reliability. The results of the validity test showed that all statement items had a calculated r value greater than the r value in the table and a significance level below 0.05. In contrast, the reliability test yielded a Cronbach's Alpha value above 0.60 for all research variables, indicating that the instrument was suitable for use. Data analysis was performed using multiple linear regression in IBM SPSS. Partial testing results indicate that work discipline, Competence, and employee empowerment each have a positive and significant effect on employee performance. Simultaneous testing also shows that the three independent variables together have a substantial effect on employee performance. The high coefficient of determination value indicates that most of the variation in employee performance can be explained by the variables of work discipline, Competence, and employee empowerment. Thus, improving employee performance can be achieved through strengthening work discipline, developing Competence, and sustainable employee empowerment.